Islamic Social Finance in Indonesia: Literature Review - Rufaedah, Dina Anisya; Patih, Husnama (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The development of the Islamic financial sector has grown rapidly. This can be seen from the development of Islamic finance research, which continues to grow every year. As highlighted in previous research, there are still gaps in our knowledge of what and how Islamic finance will evolve, especially in Islamic social finance. This research analyzes the evolution of the literature from 2013 to 2025 to find out how to fill the knowledge gap in the field of Islamic social finance. This research uses two methods, namely bibliometrics and Systematic Literature Review (SLR). The data used in the analysis is secondary data taken from the Scopus web. The results of bibliometric analysis show that the last 13 years of Islamic social finance research have increased by 80%, with the main focus on Islamic banks, zakat, and waqf. Next, a content analysis of the findings of the four main research streams we conducted. Finally, we present four research questions that can be explored in the future. The findings have a number of implications for the state of the Islamic social finance literature, including study gaps and potential future research initiatives.